Easy regulation of chitosan-based hydrogel microstructure with citric acid as an efficient buffer. (15th January 2023) - Li, Keyi; Yang, Xueting; Dong, Xin; Cao, Hongyan; Zhuang, Shujuan; Gu, Xiangling
Abstract: Being an important soft material, the chitosan-based hydrogel exhibits colorful features and widespread applications stemmed mainly from its intrinsic microstructure. In particular, the design of hydrogels with oriented channel structures is of significance importance. In this paper, polyvinyl alcohol (PVA)/chitosan (CS)/MXene-CA hydrogels with directional channel structure were obtained by simple freezing and thawing method with citric acid (CA) as a buffer. The introduction of CS increased the tensile strength of PVA hydrogel from 5.38 kPa to 29.22 kPa. The uniform distribution of MXene was efficiently enhanced within the constructed channel microstructure, and conductivity was increased to 1.91 S/m. The response time of the flexible sensor based on the hydrogel was 200 ms. It can sensitively detect large-scale deformation (blending of joints), small-scale activity (frowning), and electrocardiogram. Therefore, the paper provided an efficient way to regulate the microstructure in hydrogel network and enhance the uniform dispersion of functional nanomaterials. Graphical abstract: Unlabelled Image